An educational intervention program on knowledge about oral hygiene measures (Bangladesh Journal of Medical Science, 2014)
Background: Health education is a process of transmission of knowledge and skills necessary for improvement in quality of life. Objectives: The purpose of this quasi-experimental study was to evaluate the oral hygiene related knowledge among the population in a selected community before and after health education. Materials and Methods: A total of 106 respondents were taken purposively at South Pirerbag of Dhaka city. Baseline data were collected by pre-tested structured questionnaire. An educational intervention program was conducted by dividing the respondents into seven groups, 15 in each group; method was group discussion and lecture; poster, model of teeth and brush were the aids. Post intervention data were collected by the same questionnaire. Results: Among the respondents, 61.32% were male and 38.68% were female, mean age was 46.25 years, 35.85% had primary level education, monthly family income was Tk 5000-10000 in 66.98%. Before intervention 64.15% told that teeth should be cleaned twice daily, 62.26% told teeth should be cleaned by brush and paste and 2.83% told teeth should be cleaned after breakfast and night; whereas after intervention the result was 91.51%, 85.85% and 67.93% respectively. Before intervention 66.98% stated that tobacco is hazardous to health but 32.4% have no idea about the type of diseases that occur due to tobacco; whereas after intervention 89.62% told that tobacco is hazardous to health and most of them had idea about harmful effect of tobacco. Conclusion: Educational intervention program is effective to improve the knowledge of the respondents about oral hygiene. DOI: http://dx.doi.org/10.3329/bjms.v13i4.20589 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.421-426